2008
DOI: 10.1007/s10800-008-9481-y
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion of brass in natural and artificial seawater under anaerobic conditions

Abstract: The corrosion of brass in deoxygenated nonbuffered and buffered artificial and natural seawater was studied. The weight gains and the average corrosion rates of brass samples, immersed in both media during periods of 1 week, 1 and 3 months, were determined.The morphology of the corroded surfaces, with and without the corrosion products, was analyzed by visual observation and scanning electron microscopy (SEM). Energy dispersive spectroscopy (EDS) was used for the identification of the corrosion products and X-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…3) may be a result of the surface composition: blue is possibly copper hydroxide and chlorides (posnjakite); green is usually related to copper sulphates (atacamite, paratacamite, brochantite) and/or with basic copper chlorides; turquoise colour may be related to the presence of namuwite and/or to hydrous copper chlorosulphate (connellite); white is most likely related to zinc compounds, e.g. zinc oxide/hydroxide and zinc chloride; the gold-yellowish colour is attributed to CuCl 2 (tolbacite); pink may be attributed to zinc hydroxichloride; and the reddish colour is due to cuprite [11,[35][36][37][38][39]. The XRD results of the sheet's surface revealed presence of metallic brass as well as different oxides, including cuprite, namuwite, connellite and hydrated zinc chlorosulphate (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…3) may be a result of the surface composition: blue is possibly copper hydroxide and chlorides (posnjakite); green is usually related to copper sulphates (atacamite, paratacamite, brochantite) and/or with basic copper chlorides; turquoise colour may be related to the presence of namuwite and/or to hydrous copper chlorosulphate (connellite); white is most likely related to zinc compounds, e.g. zinc oxide/hydroxide and zinc chloride; the gold-yellowish colour is attributed to CuCl 2 (tolbacite); pink may be attributed to zinc hydroxichloride; and the reddish colour is due to cuprite [11,[35][36][37][38][39]. The XRD results of the sheet's surface revealed presence of metallic brass as well as different oxides, including cuprite, namuwite, connellite and hydrated zinc chlorosulphate (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…With the increase of corrosion rate, tin was also corroded and dissolved. Thus, only the residual copper corrosion products (oxides and chlorides of copper) were detected in region D. The elemental analysis of J, E, and F areas suggested that the corrosion of the cross-section diffused from the surface to the interior along the grain boundaries [32].…”
Section: The Determination Of Brassmentioning
confidence: 96%
“…2f. Therefore, the elemental analysis of J, E, and F areas suggested that the corrosion of the cross-section diffused from the surface to the interior along the grain boundaries [39] .…”
Section: The Determination Of Brassmentioning
confidence: 99%